PENDIDIKAN BEBAS BIAYA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH/MADRASAH - Winarsih, Sri (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2014)
Abstract: Cost isflow of resource, calculated in set of monetary which released to buy or pay inventory,service, labor,product, equipment and other goods, used for business or others interest. Education is process where someone obtain to get knowledge (knowledgeacquisition), developing skill or ability (development skill) attitude or change attitude. Education is a process of studentâs transformationin order to reach certain things as effect of follow education. Cost of education consist of (1).Direct cost is the expense from parent to learn, example: cost of the text book,practice etc.(2).Indirect costis the expense from parent, people or governmentwhich indirect relate to learning process, for example: levyingthe building, public utilities, canteen, school health unit, etc.ÙÙØ®Øµ:Â  Ø§ÙØªÙØ§ÙÙÙ ÙÙ Ø§ÙÙÙØ§Ø±Ø¯ Ø§ÙÙØØ³ÙØ¨Ø© ÙÙ ØØ³Ø§Ø¨ Ø§ÙØ¹ÙÙØ© Ø§ÙÙØªØµØ±ÙØ© ÙÙØ¨ÙØ¹ Ø£Ù Ø¯ÙØ¹ Ø§ÙØ£Ø´ÙØ§Ø¡ Ø§ÙÙØ¹Ø¯Ø©Ø ÙØ§ÙØ¹ÙÙØ ÙØ§ÙØ¹ÙÙØ§ÙØ ÙØ§ÙØ§ÙØªØ§Ø¬Ø ÙØ§ÙØ£Ø¯ÙØ§ØªØ ÙØºÙØ±ÙØ§ ÙÙ Ø§ÙØ£Ø´ÙØ§Ø¡ Ø§ÙÙØ³ØªØ¹ÙÙØ© ÙÙØµÙØØ© Ø§ÙØªØ¬Ø§Ø±Ø© Ø£Ù ØºÙØ±ÙØ§. ÙØ§ÙØªØ±Ø¨ÙØ© ÙÙ Ø¹ÙÙÙØ© ÙØØµÙ ÙÙÙØ§ Ø§ÙÙØ±Ø¡ Ø¹ÙÙ Ø§ÙÙØ¹Ø§Ø±Ù ÙØ§ÙÙØ¹ÙÙÙØ§ØªØ ÙØªÙÙÙØ© Ø§Ø³ØªØ¹Ø¯Ø§Ø¯Ø§ØªÙ ÙÙÙØ§Ø¡Ø§ØªÙØ ÙØ³ÙÙÙÙØ§ØªÙ. ÙØ§ÙØªØ±Ø¨ÙØ© ÙØ°ÙÙ Ø¹ÙÙÙØ© Ø§ØµÙØ§Ø Ø§ÙØªÙØ§ÙÙØ° ÙÙØØµÙ Ø¹ÙÙ Ø§ÙØ£Ø´ÙØ§Ø¡ Ø§ÙØ®Ø§ØµØ© ÙØªÙØ¬Ø© Ø¹ÙÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØªÙ Ø§ØªØ¨Ø¹ÙØ§. ÙØ«ÙØ© ØªÙØ§ÙÙÙ ØªØ±Ø¨ÙÙØ© ÙÙÙ : 1) Ø§ÙØªÙØ§ÙÙÙ Ø§ÙÙØ¨Ø§Ø´Ø±Ø©Ø ÙÙ Ø§ÙØªÙØ§ÙÙÙ Ø§ÙØªÙ Ø¯ÙØ¹ÙØ§ Ø§ÙØ·Ø§ÙØ¨ Ø£Ù ÙØ§ÙØ¯Ø§Ù ÙÙÙÙØ© Ø¹ÙÙÙØ© Ø§ÙØªØ¹ÙÙ ÙØ§ÙØªØ¹ÙÙÙØ ÙØ¹ÙÙ Ø³Ø¨ÙÙ Ø§ÙÙØ«Ø§Ù ÙØ´Ø±Ø§Ø¡ Ø§ÙÙØªØ¨Ø ÙØ§ÙØªØ±Ø¨ÙØ© Ø§ÙØªØ¯Ø±ÙØ¨ÙØ© ÙØºÙØ±ÙØ§Ø 2) Ø§ÙØªÙØ§ÙÙÙ ØºÙØ± Ø§ÙÙØ¨Ø§Ø´Ø±Ø©Ø ÙÙÙ Ø§ÙØªÙ ÙØ¯ÙØ¹ÙØ§ Ø§ÙØ·Ø§ÙØ¨ Ø£Ù ÙØ§ÙØ¯Ø§ÙØ Ø£Ù Ø§ÙÙØ¬ØªÙØ¹Ø Ø£Ù Ø§ÙØÙÙÙØ© ÙÙÙÙÙØ© Ø§ÙØªÙ ÙØ§ ØªØ±ØªØ¨Ø· ÙØ¨Ø§Ø´Ø±Ø© Ø¨Ø¹ÙÙÙØ© Ø§ÙØªØ¹ÙÙ ÙØ§ÙØªØ¹ÙÙÙØ ÙØ«Ù Ø§ÙØªÙØ§ÙÙÙ ÙØ¨ÙØ§Ø¡ Ø§ÙÙØ¯Ø§Ø±Ø³Ø Ø£Ù Ø§ÙÙØ³Ø§Ø¦Ù Ø§ÙØ¹Ø§ÙØ©Ø Ø£Ù Ø§ÙÙÙØµÙ ÙÙÙØµØ¯Ø±Ø³Ø©Ø Ø£Ù Ø¹ÙØ§Ø¯Ø© Ø§ÙØµØØ© ÙØºÙØ±ÙØ§.Â Keywords: Pendidikan, bebas biaya, mutu, sekolah.